2016
DOI: 10.1007/s10140-016-1425-y
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal CT pulmonary angiography in the emergency department: a retrospective analysis of outcomes in a large academic medical center

Abstract: Optimal CT pulmonary angiography (CTPA) is a prerequisite for accurate diagnosis and management of suspected venous thromboembolic disease (VTE) in the emergency department (ED). However, a certain proportion of CTPA studies are diagnostically limited or non-diagnostic due to various technical causes. In this study, we analyze the incidence and cause of suboptimal CTPA studies in the ED and assess the need for additional imaging. Reports of 1444 consecutive CTPAs performed in an ED on adult patients over a 25-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…We found a fairly high rate of suboptimal CTPA, 19.3%. This number is substantially higher than the 4% found in a study by Bates et al that used a similar definition of “suboptimal.”9 The chart review methods in that study were not as rigorous as ours, and we suspect the true suboptimal rate is higher than 4%.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We found a fairly high rate of suboptimal CTPA, 19.3%. This number is substantially higher than the 4% found in a study by Bates et al that used a similar definition of “suboptimal.”9 The chart review methods in that study were not as rigorous as ours, and we suspect the true suboptimal rate is higher than 4%.…”
Section: Discussionmentioning
confidence: 70%
“…However, impressions stating inability to exclude subsegmental PE were not included as suboptimal, since subsegmental PEs may not need to be treated 8. Note that our definition of “suboptimal” is consistent with prior literature on this topic 9…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Attenuation along a vessel may be disturbed by beam hardening artifacts from contrast originating from abutting vasculature, wires, or medical devices [33]. Studies have found 0.5% to 12.1% of CTPA studies to be non-diagnostic [78,[100][101][102][103][104][105][106][107][108][109][110][111][112].…”
Section: Ct Pulmonary Angiography For Pre-procedural Planningmentioning
confidence: 99%
“…Motion artifact is a major cause of indeterminate CTPA examinations when using a 4 to 16-slice scanner, but this has been improved with a 64-slice scanner, in some reports in the literature. 9,34,46 In patients who cannot do inspiratory breath holding, shallow free breathing can be effective and does not cause motion artifact, when using dualsource high-pitch CTPA. 47 Lowering the pitch by using thicker collimation can also decrease photon starvation, and thus improve SNR 2,25 (Figure 4).…”
Section: Challenges Of Imaging In Obesitymentioning
confidence: 99%